Advancements in artificial organs and prosthetics: bridging the gap between biology and technology - Wazid, Meer Zeshanul; Chowdhury, Jubaida Niyasa; Ome, Rejwana Habib (Brac University Research For Development Club (BURED), 2024)
Cataloged from PDF version of the article.